Dosing, efficacy, and safety of recombinant factor VIIa (rFVIIa) in pediatric versus adult patients: The experience of the Hemostasis and Thrombosis Research Society (HTRS) Registry (2004–2008)1. Issue 7 (17th January 2013) - Neufeld, Ellis J.; Saxena, Kapil; Kessler, Craig M.; Cooper, David L.; ,
Abstract Background The longitudinal registry of the Hemostasis and Thrombosis Research Society (HTRS) provided data on treatment of bleeding episodes for pediatric and adult patients with congenital hemophilia complicated by inhibitors to factor VIII or IX. Procedure Data from 2, 041 recombinant factor VIIa (rFVIIa)‐treated episodes were recorded in the HTRS Registry between January 2004 and November 2008 and included in this retrospective analysis. The authors compared dosing, efficacy, and safety in 1, 712 episodes in 284 children (age ≤18 years) and 329 episodes in 145 adults (>18 years). Results Patients were predominantly non‐Hispanic white (52% of children, 68% of adults) with hemophilia A (91%). The majority of bleeds were spontaneous (55% pediatric, 69% adult) and occurred in the joint (55% pediatric, 65% adult). rFVIIa was used first line in most episodes (90% pediatric, 93% adult); 27% of episodes in both age groups were treated with a single dose. Children and adults received comparable median number of doses (three) and duration of therapy (1 day); adults had lower median [range] initial doses (90 [46–400] µg/kg vs. 120 [37–400] µg/kg) and median [range] total doses (270 [46–21, 392] µg/kg vs. 480 [50–43, 200] µg/kg) than children. Effectiveness was comparable between the groups. No thromboembolic complications were reported. Conclusions Dosing of rFVIIa was somewhat higher in pediatric than adult patients in the HTRS registry population, with similar effectiveness. Safety assessment, demonstrating lack of thromboembolic events associated with treatment of bleeding episodes, was similar between the children and adults in this retrospective registry. Pediatr Blood Cancer 2013; 60: 1178–1183. © 2013 Wiley Periodicals, Inc.